Pengaruh Tingkat Pengungkapan Corporate Social Responsibility Terhadap Information Asymmetry Diukur Dengan Bid Ask Spread - Florensia Agatha; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
This research aimed to identify the affects of Corporate Social Responsibility disclosure level towards information asymmetry measured by using bid ask spread. Disclosure level of CSR will be measured using Sustainability Reporting Index (SRI) which will be accessed based on the Global Reporting Initiatives (GRI) guidelines. This research also used 2 additional controlled variables, that were firm value measured using Tobin’s Q and firm age. The research done on firms listed on the Bursa Efek Indonesia (BEI) and disclosed sustainability reporting on GRI site, with a total of 130 observations as the regression model. The result of this research showed there was a significant negative affect of CSR disclosure level on information asymmetry. Firm value that measured by using Tobin’s Q had a significantly positive effect on information asymmetry, while firm age has no affect on information asymmetry.